PRIMARY COMMUNICATIONS OF THE COUNSELLOR WITH THE CUSTOMER IN MANAGEMENT CONSULTATION - Yu. D. Krasovskii (Вестник университета)
Four possible variants of the consultant’s strategies at the initial stage of management consulting of top management of companies at the stage of forming hypotheses and their adjustment in the process of subsequent use of author’s social techniques have been presented in a digital format. A feature of such researches is the subsequent development of simulation models in a digital visual graphic format. The main attention has been paid to the description of research consult-development in the analysis of managerial situations. The most authoritative researchers in the Russian practice of management consulting have been adduced in the list of references.